An effective treatment of dark lip by frequency-doubled Q-switched Nd:YAG laser - Somyos Kunachak (2018)
BACKGROUND. Dark lip is a common cosmetic problem in Southeast Asia. There is no known effective treatment. OBJECTIVE. To propose an effective method for treating dark lips of varying causes with frequency-doubled Q-switched Nd: YAG laser. METHODS. Seventy patients with dark lip, of which 22 were congenital, 24 acquired, and 24 of uncertain cause, were treated by frequency-doubled Q-switched Nd:YAG laser at a fluence of 2-3.5 J/cm2 (mode 2.5 J/cm2) after application of topical anesthesia. The endpoint of treatment was complete clearance of the pigment. Follow-up time was 24-36 months (mean 29 months). RESULTS. All patients attained complete clearance of the lesion after an average of 2.5 treatments in the congenital group, 2.2 treatments in the acquired group, and 1.8 treatments in the group with uncertain etiology. The mean (±SD) number of treatments required by the whole group was 2.1 ± 1.4. Recurrence was observed in one case of congenital origin 3 months after the last treatment. In the remaining cases, results persisted up to the time of follow-up. Herpes simplex reactivation was noted in one case 3 days after treatment. There was no dyschromia, scar formation, or change of skin texture. CONCLUSION. Dark lip can be effectively treated by frequency-doubled Q-switched Nd:YAG laser without major adverse effects.